Effect of chrysin on methotrexate‐induced testicular damage in rats. (1st October 2018) - Belhan, Saadet; Çomaklı, Selim; Küçükler, Sefa; Gülyüz, Fetih; Yıldırım, Serkan; Yener, Zabit
Abstract: This study was conducted on 28 male Wistar albino rats to determine the effects of chrysin on methotrexate‐induced damage to testicular tissue. Rats were grouped into four groups of seven rats reach: Group 1 ( n = 7) was the control group to which no drugs were administered; this group was only provided with food and water. Group 2 ( n = 7) was administered 20 mg/kg of methotrexate once intraperitoneally. Group 3 ( n = 7) was administered 50 mg/kg of chrysin for 7 days orally. Group 4 ( n = 7) was administered 20 mg/kg of methotrexate once intraperitoneally, followed by oral administration of 50 mg/kg of chrysin for 7 days. At the end of the experiment, rats were anaesthetised, rat testes were removed, and spermatozoon was obtained from the cauda epididymis. It was determined that sperm count and motility, glutathione peroxidase, superoxide dismutase and catalase activities decreased in the methotrexate group, whereas malondialdehyde, tumour necrosis factor‐α, interleukin‐1β and nuclear kappa factor B expression levels increased. Furthermore, damage to tubulus seminiferus structures and affusion in germ cells was identified. In the methotrexate + chrysin administered group, sperm count improved, biochemical enzyme levels increased, and structural improvements were observed in testicular tubules. These findings demonstrated that chrysin plays a protective role in testicular damage in rats.